TRI HANAKARA AS A SPATIAL LAYOUT PERSISTENCE CONCEPT OF BALUWARTI SETTLEMENT IN SURAKARTA - Tri Hartanto; Tony Atyanto Dharoko; Yoyok Wahyu Subroto (DIMENSI (Journal of Architecture and Built Environment), 2020)
Elements of settlement spatial layout (physical aspect) and community’s social-cultural life with any rites (non-physical aspect) are still performed by some people in Baluwarti Settlement until today, leading to a distinctive peculiarity. It is this peculiarity that makes Baluwarti Settlement environment located inside the court (palace) different from other settlements (outside the court) in Surakarta. Considering the qualitative research paradigm and historical reading method, this research could find out that the spatial layout concept of Baluwarti Settlement namely Tri Hanakara. In which the kings reigning after Paku Buwana III constructed this Baluwarti settlement to forward the previous King’s wish.